The Role of Fathers\' Involvement in Parenting and Adolescent Social Harms: A Narrative Review - Maryam Mohammadi; Fateme Moshirenia; Moradali Zareipour; Shahnaz Kohan; Zahra Boroumandfar (Journal of Community Health Research, 2024)
Background: In today's society, the issue of fatherhood and involvement in the upbringing of children has been emphasized. The study aimed to investigate the impact of fathers' involvement in parenting on the social victimization of adolescents. Methods: The present research utilized a narrative review methodology, with technical terms being explained at the beginning. Relevant sources were identified by conducting searches on reputable academic databases, including ISI Web of Knowledge, PubMed, Google Scholar, ProQuest, Ovid, Elsevier, SID, and Magiran, covering the period from 2000 to 2023. The search keywords encompassed various related themes, such as fatherhood, absent fathers, childrearing, adolescents, father involvement, engagement, social problems, and Boolean operators (AND, OR, NOT). Compilation procedures were conducted according to the SANRA checklist. In the initial search, 162 articles were obtained. After removing duplicates and evaluating their titles and abstracts, 9 articles were selected for the review. Results: Based on the findings of this literature review, paternal involvement in child-rearing is shown to positively affect the intellectual, moral, and social development of adolescents. Conversely, the absence of a father figure has been linked to negative outcomes such as drug addiction, decreased academic performance in both school and university, anti-social attitudes, separation anxiety, aggression, feelings of insecurity, and negative thoughts in teenagers. Conclusion: The involvement of fathers in upbringing of their children fosters critical thinking and reinforces children's empowerment in making pivotal decisions, while simultaneously acting as a safeguard against social risks.